Empowering women-owned businesses in the era of digital transformation: a review of the opportunities and challenges - Hazudin, Siti Fahazarina; Sabri, Mohamad Fazli; Awang Kader, Mohd Aidil Riduan; Ishak, Maisarah (Human Resource Management Academic Research Society, 2021)
This paper aimed to discuss the opportunity and challenges that are faced by women entrepreneurs in the current digital transformation development. A summary of scholarly works alongside the discussion of some important findings based on the centred issue was presented in the current paper. The analysis was focused on explaining the role of the most important digital business solution, namely social media. The major challenges of pursuing digital alternative were also discussed, varying from a traditional gender issue to emerging digital pressures. This paper provides the relevant academic explanation of the underlying requirements for creating successful women entrepreneurs in digital business, while the highlighted pitfalls can help them avoid incidentally occurrence of business failures.